Aplikasi Inventori Berbasis Web pada Toko Ian Lim - khriswandy setiawan; Tony (Computatio : Journal of Computer Science and Information Systems, 2026)
Toko Ian Lim is one of the distributors in Bangka Belitung Province which is engaged in the sale of basic necessities. With the large stock of goods in the main warehouse, problems arise such as not knowing the availability of goods in the main warehouse. Designing a Web-Based Inventory Application at Toko Ian Lim using the SDLC (Software Development Life Cycle) Waterfall model, Hypertext Preprocessor (PHP) programming language and MySQL database The result of this research is that this web becomes a means of information, and the main sales transaction for Inventory at Toko Ian Lim. This web application is expected to increase sales turnover and reputation at Toko Ian Lim. In the design of the inventory application at Toko Ian Lim, it can receive information about the stock of goods in the warehouse, place orders for goods in the warehouse for customers, view incoming and outgoing goods, warehouse admins can manage warehouse data in the database and can manage item reports.